An experiment on partnership protocols for bilateral trade with incomplete information - Barry Sopher; Revan Sopher (Rutgers University, Department of Economics, 2012)
We study experimentally partnership protocols of the sort proposed by Kalai and Kalai (2010), for bilateral trade games with incomplete information. We utilize the familiar game analyzed by Chatterjee and Samuelson (1983) and Myerson and Sattherwaite (1983), with a buyer and seller with value and cost independently distributed uniformly on (0,100). The usual rules of the game are for the buyer and seller to submit price bids and asks, and for trade to occur if and only if the buyer's bid price exceeds the seller's ask price, in which case trade occurs at the average of the bid and the ask price. We compare the efficiency of trade and the nature of bid functions in this standard game to those in other versions of the game, including games in which cheap talk is allowed prior to trade (either before or after the traders know their own information, but without knowing each others' information), games with the formal mechanisms proposed by Kalai and Kalai available as an option for the traders to use, and games with both the mechanisms and cheap talk available. We consider both ex ante and interim mechanisms. That is, traders simultaneously choose whether to opt in to the mechanism either prior to knowing their own information, or after knowing their own information. In the last two versions of the game, cheap talk takes place prior to the opt-in decision. We find that the formal mechanisms significantly increase the efficiency of trade in both the ex ante and interim cases. Specifically, in the baseline game, traders captured 73% of the available surplus (compared to a theoretical maximum of 84% possible with optimal strategies). Efficiency rises to 87% and 82% for the ex ante and interim mechanisms, respectively, and further rises to 90% and 84% when cheap talk is also allowed with the mechanisms. When only cheap talk is allowed, traders capture 81% (for ex ante talk), but only 70% (for interim talk). On average, 55% of trading pairs opt in to mechanisms when they are available.
Keywords: C9; C7; 330; Experiments; Bilateral Trade; Protocols; experiments; bilateral trade; protocols